2002
DOI: 10.1177/016502540202600111
|View full text |Cite
|
Sign up to set email alerts
|

Social creativity: A cross-sectional study of 6- to 11-year-old children

Abstract: We assessed children’s social creativity through interviews during which participants imagined original solutions to interpersonal problems. In addition, we compared performances in the social domain with those obtained in object-oriented problem-solving tasks such as the Unusual Uses of a Box creativity test designed by Torrance (1974) and the Similarities subtest of the WISC (1996). A total of 88 French children participated in this study. First, we observed links between social creativity tasks as well as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 44 publications
2
45
0
4
Order By: Relevance
“…Although several Western scholars have argued that originality is the crux of creativity (Boden, 1990;Barron, 1963;Runco & Jaeger, 2012), Taiwanese students of creativity, as influenced by Chinese culture, would appear to have slightly different implicit theories of creativity. This observation echoes those of other International Journal of Culture and History ISSN 2332-5518 2014 cross-cultural studies (Lubart, 1990;Mouchiroud & Lubart, 2002;Niu & Sternberg, 2001), all of which found that Eastern and Western peoples possess a different conception of creativity to some extent. This idea deserves more attention from future cross-cultural studies, which might help to untangle various nuances in the perception of creativity in different parts of the world.…”
Section: It Would Be Worthwhile To See How the Results Might Differ Isupporting
confidence: 85%
“…Although several Western scholars have argued that originality is the crux of creativity (Boden, 1990;Barron, 1963;Runco & Jaeger, 2012), Taiwanese students of creativity, as influenced by Chinese culture, would appear to have slightly different implicit theories of creativity. This observation echoes those of other International Journal of Culture and History ISSN 2332-5518 2014 cross-cultural studies (Lubart, 1990;Mouchiroud & Lubart, 2002;Niu & Sternberg, 2001), all of which found that Eastern and Western peoples possess a different conception of creativity to some extent. This idea deserves more attention from future cross-cultural studies, which might help to untangle various nuances in the perception of creativity in different parts of the world.…”
Section: It Would Be Worthwhile To See How the Results Might Differ Isupporting
confidence: 85%
“…Como mencionan Krumm y Lemos (2012) "los estudios en relación a la popularidad sociométrica muestran que los niños con buena adaptación social presentan buenos niveles de autoconcepto, son respetuosos y perseverantes, emocionalmente estables, confiados, seguros de sí mismos" (p. 45), teniendo motivación para la tarea, denotando las mismas característica de la personalidad de los niños más creativos (Krumm, 2012;Krumm y Lemos, 2012;Garaigordobil, 1993;Pérez y Garaigordobil, 2004;Shiner y Masten, 2002). Estos niños tienen más recursos y habilidades para interactuar con los otros, pares y grupos, así como para manejarse en diferentes ambientes sociales (Mouchiroud y Lubart, 2002), inclusive, son reconocidos por sus compañeros como creativos (Garaigordobil, 2005).…”
Section: Introductionunclassified
“…Among these theories, Gardner's theory of Multiple Intelligences and Csikszentmihalyi's system perspective of creativity is most typical. Social creativity is a special sort of creativity in social interaction or social activities where a person proposes or solves social problems in the novel, special, appropriate and valid approaches, and it is correspondent to artistic creativity or scientific creativity [7]. In fact, in the Theory of Multiple Intelligences, interpersonal intelligence is regarded as the outstanding performance of social creativity.…”
Section: B Social Creativitymentioning
confidence: 99%
“…In fact, in the Theory of Multiple Intelligences, interpersonal intelligence is regarded as the outstanding performance of social creativity. Mouchiroud et al (2002) carried out a study to investigate social creativity of primary school children in France, pointing out that social creativity was a relatively independent structure. Gu et al (2007Gu et al ( , 2010) also found that children's social creativity was a more coherent and integrated structure in the context of Chinese culture through a series of studies about social creativity of primary school children [8][9][10].…”
Section: B Social Creativitymentioning
confidence: 99%